2015
DOI: 10.1007/s10900-015-0104-3
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Receiving Follow-Up Eye Care and Detection of Non-Glaucomatous Ocular Pathology in the Philadelphia Glaucoma Detection and Treatment Project

Abstract: This cross-sectional study aimed to evaluate adherence rates and identify barriers to receiving follow-up eye care in participants diagnosed with significant non-glaucomatous eye pathology in the Philadelphia Glaucoma Detection and Treatment Project. This community-based project aimed to improve detection, management, treatment, and follow-up eye care of individuals at high risk for glaucoma in community-based settings. Participants throughout Philadelphia, Pennsylvania, USA were enrolled. After a comprehensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…Adherence in this study was defined as 1 or more visits within 1 year of diagnosis, and these rates were similar to what we observed for the same outcome in our intervention group (74.4%). Although the UC rate was much lower in our study, it is consistent with low rates seen in another recent study (26).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Adherence in this study was defined as 1 or more visits within 1 year of diagnosis, and these rates were similar to what we observed for the same outcome in our intervention group (74.4%). Although the UC rate was much lower in our study, it is consistent with low rates seen in another recent study (26).…”
Section: Discussionsupporting
confidence: 93%
“…Future studies could consider combining additional interventions to further increase rates of adherence to follow-up eye care. Other interventions that may show promise include providing incentives such as free eyeglass prescriptions or free eyeglasses (26) and providing other financial incentives to encourage at-risk participants to return for follow-up eye examinations (12). The costs of the screening phase have been previously reported (22); the costeffectiveness of our adherence intervention is being evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…5 Other studies of high-risk populations also found that rates of adherence to recommended follow-up care were below 50%, even when major barriers to eye care such as cost and accessibility were minimized. 6–8 These low rates of eye care utilization can be major obstacles to combating vision problems in the United States (US) such as the high prevalence (~2.4 million Americans 9 ) of undiagnosed and untreated glaucoma.…”
Section: Introductionmentioning
confidence: 99%
“…One unique nding in this study, and probably the most important, is having the perceived need to followup with an ophthalmologist during COVID-19 lockdown as a signi cant negative predictor of participants' HRQoL. Even in normal situations out of health pandemics and its associated lockdowns, many vision patients tend not comply with their ophthalmic follow-up appointments which might negatively impact their vision health (23)(24)(25). Although following up with an ophthalmologists is highly recommended in the literature(54), this was not easy for the majority of this study participants during the lockdown.…”
Section: Discussionmentioning
confidence: 86%
“…Even during normal situations out of pandemics and lockdowns, the adherence with ophthalmologic follow-up care was not found optimal among many vision patients. (23)(24)(25). Lack of adherence with eyecare follow-up might lead to vision deterioration, which is usually associated with decreased levels of HRQoL and increased levels of mental health symptoms (13,14).…”
Section: Introductionmentioning
confidence: 99%